Prevalence, Pattern and Outcome of Blood Transfusion: A Private Paediatric Hospital Experience - Boma A West; Josephine E. Aitafo (Pediatric Review: International Journal of Pediatric Research, 2023)
Introduction: Blood transfusion is an essential component of Pediatric care world-wide especially in developing countries. Knowledge about its’ prevalence and pattern is vital in promoting its’ judicious use.Purpose:  To ascertain the prevalence, pattern and outcome of blood transfusion in a private pediatric hospital in south-south Nigeria.Materials and Methods: A retrospective study was carried out over a 1-year period on children(0-17years) admitted and transfused. Relevant data was retrieved from the hospitals’ Health Management System and analysed.Results: Of 1689 admissions, 69 were transfused giving a prevalence rate of 4.1% with male predominance (M:F ratio of 1.5:1). Eighty-eight blood transfusions were done giving a ratio of 1.3 transfusions/child.  Transfused children were mainly 1–12 months of age with mean age of 3.848 ± 4.890months. Most blood transfusions took place within the first 5 hours of prescription and occurred mostly at night. Sedimented cells were mainly used 49(71.0%). Nine(13.0%) children had blood transfusion reactions of which 5(60.0%) had fever. The commonest diagnosis among children transfused were severe anaemia 61(46.9%), prematurity 22(16.9%), sickle cell anaemia 8(6.2%) and sepsis 7(5.4%). Twelve(17.4%) children transfused died. The age of children, type of blood transfused and number of transfusions carried out were significantly associated with the outcome of blood transfusion.Conclusion: The prevalence of blood transfusion was 4.1%. Commonest diagnosis were severe anaemia, prematurity, sickle cell anaemia and sepsis with mortality rate of 17.4%. It is therefore important to equip private hospitals with functional blood bank services so as to reduce childhood morbidity and mortality.